Dynamic stretching is effective as static stretching at increasing flexibility - Coons, J. M.; Gould, C. E.; Kim, J. K.; Farley, R. S.; Caputo, J. L. (Journal of Human Sport & Exercise, 2017)
This study examined the effect of dynamic and static (standard) stretching on hamstring flexibility. Twenty-five female volleyball players were randomly assigned to dynamic (n = 12) and standard (n = 13) stretching groups. The experimental group trained with repetitive dynamic stretching exercises, while the standard modality group trained with static stretching exercises. The stretching interventions were equivalent in the time at stretch and were performed three days a week for four weeks. Both stretching groups showed significant improvements (P < .001) in range of motion (ROM) during the intervention. However, no difference in gains in the range of motion between stretching groups was observed. It was concluded that both dynamic stretching and standard stretching are effective at increasing ROM.